2023
DOI: 10.17912/micropub.biology.000727
|View full text |Cite
|
Sign up to set email alerts
|

Germline TFAM levels regulate mitochondrial DNA copy number and mutant heteroplasmy in C. elegans

Abstract: The mitochondrial genome (mtDNA) is packaged into discrete protein-DNA complexes called nucleoids. mtDNA packaging factor TFAM (mitochondrial transcription factor-A) promotes nucleoid compaction and is required for mtDNA replication. Here, we investigate how changing TFAM levels affects mtDNA in the Caenorhabditis elegans germ line. We show that increasing germline TFAM activity boosts mtDNA number and significantly increases the relative proportion of a selfish mtDNA mutant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The variant uaDf5 is an exemplary model selfish mitochondrial genome, undergoing positive intraorganismal selection at the expense of host fitness. 26,30,32,[34][35][36]38 We expand the understanding of uaDf5 in numerous key ways. Prior studies have found that uaDf5 proliferates not merely in spite of, but at least partly because of, its negative effect on mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The variant uaDf5 is an exemplary model selfish mitochondrial genome, undergoing positive intraorganismal selection at the expense of host fitness. 26,30,32,[34][35][36]38 We expand the understanding of uaDf5 in numerous key ways. Prior studies have found that uaDf5 proliferates not merely in spite of, but at least partly because of, its negative effect on mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…26,32,34,36,41 Moreover, proteins with a more direct role in mitochondrial biogenesis and mtDNA replication, such as POLG and the mtDNA-associated protein TFAM, or that promote binding of replication machinery to mtDNA, reportedly mediate selfish mtDNA proliferation. 30,32,36 Conversely, genes involved in mitochondrial fission and autophagy reportedly contribute to intra-organismal selection against mutant mtDNA. 34,36,37,39,[58][59][60] Given these findings, we propose that host genotypes and environmental factors, especially those linking physiological stress with mtDNA replication and turnover, will be important determinants of the cooperator-cheater dynamics described here and should be considered in future research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations